2000
DOI: 10.2337/diabetes.49.10.1691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary energy restriction on glucose production and substrate utilization in type 2 diabetes.

Abstract: A total of 8 obese subjects with type 2 diabetes were studied while on a eucaloric diet and after reduced energy intake (25 and then 75% of requirements for 10 days each). Weight loss was 2, 3, and 3 kg after 5, 10, and 20 days, respectively; all of the weight lost was body fat. Fasting blood glucose (FBG) levels fell from 11.9 ± 1.4 at baseline to 8.9 ± 1.6, 7.9 ± 1.4, and 8.8 ± 1.3 mmol/l at days 5, 10, and 20, respectively (P < 0.05, baseline vs. 5, 10, and 20 days). Endogenous glucose production (EGP) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 46 publications
4
38
0
1
Order By: Relevance
“…Prior studies have not directly examined the effects of orlistat on IS measured by a criterion method such as euglycemic insulin infusion. Improved IS is clearly a desirable metabolic effect of weight loss, and prior studies have found this is related to negative energy balance as well as loss of adipose tissue (32)(33)(34). However, because the rates and amounts of weight loss in the orlistat and placebo arms of the intervention were highly comparable, these important factors do not account for the differential effect.…”
Section: Dietary Assessmentsmentioning
confidence: 80%
“…Prior studies have not directly examined the effects of orlistat on IS measured by a criterion method such as euglycemic insulin infusion. Improved IS is clearly a desirable metabolic effect of weight loss, and prior studies have found this is related to negative energy balance as well as loss of adipose tissue (32)(33)(34). However, because the rates and amounts of weight loss in the orlistat and placebo arms of the intervention were highly comparable, these important factors do not account for the differential effect.…”
Section: Dietary Assessmentsmentioning
confidence: 80%
“…Therefore, HGP is not a constant, like serum sodium concentration or osmolality, but depends upon recent CHO balances. Studies in rats , normal humans Clore et al, 1995) and type II diabetes mellitus (Wing et al, 1994;Kelley et al, 1993;Christiansen et al, 1995) have documented the responsiveness of HGP to recent CHO energy intake. Biochemical mechanisms for this adaptation have been proposed.…”
Section: Metabolic Response To Surplus Cho Energy Intake In Humans: Tmentioning
confidence: 99%
“…The implication for diseases related to insulin resistance, including type II diabetes, have not been fully explored, although this metabolic adaptation appears to represent the physiologic basis of the therapeutic response to energy restriction (`weight loss') in type II diabetes (Wing et al, 1994;Kelley et al, 1993;Christiansen et al, 1995). (iii) The liver is therefore responsible for whole-body fuel selection in the post-absorptive state.…”
Section: Metabolic Response To Surplus Cho Energy Intake In Humans: Tmentioning
confidence: 99%
“…The absolute contribution to plasma glucose from glycogen (glycogenolysis) was calculated as EGP-absolute GNG. Fasting plasma glucose clearance was calculated as the rate of disappearance of glucose (identical to R a glucose under steady-state conditions) divided by the fasting plasma glucose concentration [23]. HOMA-insulin resistance (HOMA-IR) and HOMA-beta cell function (HOMA-B) were calculated as previously described [24].…”
Section: Methodsmentioning
confidence: 99%